Connie Rahakundini Bakrie's Political Communication on the Russia-Ukraine Conflict: A Critical Discourse Analysis of the Helmy Yahya Bicara YouTube Channel (Oratio Directa, 2022)
This study examines Connie Rahakundini Bakrie's political communication concerning the Russia-Ukraine conflict in an episode of the Helmy Yahya Bicara YouTube channel. It uses a qualitative descriptive approach and critical discourse analysis informed by Halliday's view of language as social action. The unit of analysis is the speaker's verbal discourse in the video titled Invasi Rusia-Ukraina, Akankah Menyulut PD-III? The findings identify five thematic clusters: explanations of Russia's actions and Ukraine's position; criticism of United States and NATO hegemony; assessments of global war, sanctions, and interdependence; regional equilibrium and Indonesian national interests; and leadership, history, and geopolitical literacy. The discourse constructs the speaker as a realist and nationalist academic while encouraging Indonesia to pursue strategic autonomy and a balancing role. These findings describe the framing within the selected video and do not independently verify its geopolitical claims.
Keywords: Political communication; Critical discourse analysis; Russia-Ukraine; YouTube; Geopolitics